Peran Modal Sosial dalam Melestarikan Subak Bukti Batan Badung di Desa Gulingan Kecamatan Mengwi Kabupaten Badung - I GUSTI PUTU SASTRA PUTRA KUSUMA; I WAYAN WINDIA; NI WAYAN SRI ASTITI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2018)
Role of Social Capital in Preserving Subak Bukti Batan Badung in GulinganVillage, Mengwi Sub-district, Badung Regency Subak Bukti Batan Badung is one of the subaks found in Bali. The area of Subak BuktiBatan Badung was previously 65,25 hectares and had undergone land conversion of7,25 hectares. Seeing the current development, it is highly likely that the existence ofSubak Bukti Batan Badung could be threatened. Thus, there is a need for the role ofsocial capital is preserving Subak Bukti Batan Badung. The data analysis method usedwas descriptivr qualitative.The results of this study showed that social capital owned bySubak Bukti Batan Badung to keep its sustainability was good which could be seen in:(1) the farmer’s belief in other farmers, the farmer’s belief in subak administrators,farmer’s belief in the government program and religious rituals, and the farmer’e beliefin the cooperatives, (2) the norms; awig-awig owned was not strong enough to suppressland conversion. Other norms were still strong and obeyed by all the subak member. (3)The social network owned could br said to be good, it could be seen from subak’srelationship with banjar/adat village, subak relationship with Public Work andAgricultural Departements.The suggestion that can be made from this research is toreinforce regulation accompanied bu sanction for related parties violating the awig-awigand awareness of subak members not to do land conversion.